THEORETICAL AND EXPERIMENTAL STUDY OF THE INTERIOR BALLISTICS OF A RIFLE 7.62 - Cronemberger, P. O.; Lima Jr., E. P.; Gois, J. A. M.; Caldeira, A. B. (Revista de Engenharia Térmica, 2014)
This study aims to examine theoretically and experimentally the interior ballistics of a rifle 7.62. Three theoretical methods are employed: the Vallier-Heydenreich, which is based on empirical data tables; the lumped parameters that is represented by a differential-algebraic system of equations, describing the propellant combustion, the thermodynamics of the gas inside the gun and the projectile dynamics; and the commercial software PRODAS. The theoretical solutions furnish the pressure, the projectile velocity and the projectile position inside the gun, the maximum pressure,the muzzle velocity and the total time of the interior ballistics. The experiments measure the pressure along of the time and the projectile velocity at seven meters ahead of the barrel. The proposed lumped parameter model indicates alternatives to model the energy lost and the resistance pressure functions. The theoretical solutions are compared with experiments. A thermodynamics analysis of the energy conversion in the gun is provided. The results are analyzed and the relevance of each method is highlighted.